Effects of five fungicides on mycelial growth of L. edodes, P. ostreates, F. velutipes and contaminated mold - JIANG Dong-hua (浙江大学学报. 农业与生命科学版, 2001)
Effects of five fungicides on the hypha growth of L. edodes, P. ostreates, F. velutipes and contaminated mold were studied. The results showed that the inhibition with different kinds and treatment concentrations of fungicides on the hypha growth of three edible fungi and contaminated mold had significant differences. It was proved that the Chlorothalonil and Iprodione had the strongest effects. Both of their average inhibitory rates were higher than 90%. The copper hydroxide had the least effect with an average inhibitory rate of lower than 5% in 0.667-0.883 g/L. The result also showed that the copper hydroxide and Chlorothalonil had strongest inhibition on contaminated mold. Therefore, the best fungicide for L. edodes, P. ostreates and F. velutipes cultivation was Copper hydroxide. The suitable concentration lied 0.7-0.8 g/L.